Educação Ambiental e o Trabalho com Valores: reflexões sobre uma experiência de formação continuada - Dalva Maria Bianchini Bonotto; Adriana Aparecida Dragone Silveira; Aparecida José Carlini Bonilha; Beatris Cristina Possato Gianei; Giovana Aparecida dos Santos; Luciane Aparecida de Oliveira; Patrícia Cristina Rosalen; Rosana Cristina S. Furtado Cupido (Educação: Teoria e Prática, 2007)
The present article shows the reflections of an elementary school teachers group of the Municipal Net of Rio Claro city about their experiences at an in-service teacher education program of Environment Education and the work with values. Considerations about the teacher education, teacher performance and the in-service educational programs are also presented.